Things We Like - Murray, W.; Illustrated by Aitchison, M. (London Ladybird)
Employs the frequently met words in the English language as a starting point for learning to read successfully and confidently. This title uses 36 words including 'me', 'tea', 'bed' and 'give'.
Include Color Illustrations